Classification of cognitive algorithms for managing services used in cloud computing. (24th April 2020) - Ogiela, Lidia; Takizawa, Makoto; Ogiela, Urszula
This paper presents a new idea of cognitive systems dedicated to cloud computing. Especially presents backgrounds, introduction and description of service management procedures and algorithms dedicated to cloud computing and infrastructure. Cognitive methods based on semantic description and interpretation procedures. Described idea will be dedicated to secure service management procedures, especially in the cloud and fog stages. The proposed algorithms of cognitive service management will be presented and described by use of semantic aspects. Semantic analysis is used to extract meaning of analysed data. Also, in management processes is possible to analyse meaning aspects. These kinds of analysis can be used in different application areas. This paper presents services management protocols in the cloud and in the fog. In both of these stages is possible realised management procedure by application of secure methods and protocols. This paper presents the sharing techniques for data security in cloud computing.